Polaris : leerwerkboek - Goemans, Arjan, ....-; Goyvaerts, Eric, ....-; De Cnijf, Kirsten, ....-; Luypaert, Jens, ....- (Mechelen : Plantyn, 2015)
Leerwerkboek voor het eerste en tweede jaar A-stroom
Nieuwe methode aardrijkskunde voor het GO!